Synergistic impact of macrolide resistance and H3N2 infection on M. pneumoniae outbreak in children - Jiali Chen; Yingdan Wang; Juan Cheng; Yunping Ma; Xin Zhang; Xuezhou Bai; Palizhati Rehati; Huashun Cui; Fan Wu; Qiuhui Pan; Jinghe Huang (Microbiology Spectrum)
ABSTRACT In November 2023, there was a substantial increase in the incidence of Mycoplasma pneumoniae infections in China following waves of SARS-CoV-2 Omicron variant and influenza outbreaks. This study aimed to elucidate the epidemiological features and clinical implications of M. pneumoniae infections in children and explore the potential influence of SARS-CoV-2 Omicron variants and influenza A infections on the M. pneumoniae outbreak. Among 38,668 children with lower respiratory tract infections from January to December 2023, 11,919 tested positive for M. pneumoniae, predominantly between October and December. The majority of the children with M. pneumoniae were aged 5–10 years, with type 1 strains and macrolide-resistant M. pneumoniae strains having the highest prevalence rates. Statistical analysis revealed elevated C-reactive protein, neutrophil, and monocyte levels and decreased lymphocyte, basophil, and eosinophil counts in M. pneumoniae-positive children. M. pneumoniae-positive children also presented significantly increased neutralizing antibody levels against preceding influenza A (H3N2) but not against SARS-CoV-2 Omicron variants. A parallel trend was observed between M. pneumoniae and H3N2 prevalence from June to December 2023. The emergence of macrolide-resistant strains and prior influenza A (H3N2) epidemics notably contributed to the M. pneumoniae outbreak. These findings suggested that H3N2 infection facilitates M. pneumoniae infection through various mechanisms. This study underscores the complex interactions between respiratory pathogens and highlights the need for comprehensive surveillance and response strategies.IMPORTANCEThis study identified key factors contributing to an outbreak of Mycoplasma pneumoniae that affected 11,919 children. The influencing factors included a high prevalence of macrolide-resistant epidemic strains (94.2%) and significantly higher H3N2 neutralizing antibody levels (P < 0.0001) stimulated by the preceding H3N2 influenza epidemic. These findings highlight the complex relationship between the prevalence of M. pneumoniae and H3N2 infection in children, indicating that it is necessary to consider pathogen interactions in respiratory disease management by continuously monitoring respiratory pathogens. The emergence of macrolide-resistant strains in China and the previous H3N2 influenza epidemic significantly exacerbated the severity of the M. pneumoniae outbreak. H3N2 infection potentially amplifies Mycoplasma transmission. This study elucidates the epidemiological and clinical aspects of M. pneumoniae infections in children, yields insights regarding the cause of the outbreak, and provides guidance for improving respiratory infection management.